Student educational travels as a form of independent study activity: the experience of the Library and Information Sciences Department of St. Petersburg State Institute of Culture - A. S. Krymskaya (Библиосфера, 2018)
A part of international congresses programs are professional visits (trips). Foreign publications pay a special attention to professional trips, which considers them as an instrument of cultural diplomacy. In Russia there are a few examples of organizing professional (or study) trips for students. Publications dedicated to this theme are usually of descriptive character. The experience of St. Petersburg State Institute of Culture, as well as other Russian and non-Russian universities, confirms that educational trips should be regarded as a form of independent study activity. This article attempts to determine how the tasks of study trips for students of library departments correlate with competences of the educational standard. The paper considers the experience of organizing independent student work at the Library and Information Sciences Department of St. Petersburg State Institute of Culture within the framework of educational trips to other countries. It highlights the trips objectives in the context of library and information science education as the following: establishing and developing professional and interpersonal contacts between foreign and Russian educational organizations and libraries; involving students in intercultural communication; getting professional knowledge by visits to institutions, informational conversations, excursions to organizations and institutions of professional interest; exchanging professional knowledge in the field of librarianship and the experience in library practice; meetings with foreign students, scholars and specialists; acquainting with the economic, political and cultural life of foreign countries. By providing information about educational trips «The role of the book in Gutenberg’s homeland (Germany)» and «Baltic libraries as centers of science, culture, and education (Estonia, Latvia, Lithuania)», the author demonstrates how these tasks are correlated with the competencies required by the Russian educational standard of higher education «51.03.06. Library and information activities (bachelor's level)»; outlines the stages of study trips followed by a description of the professional tasks and competencies required by the federal state educational standard of higher education mentioned above. Thus, students develop competencies through independent work. The article sums that study trips as a form of independent activity accomplish professional tasks required by the Russian educational standard of higher education, such as research and methodological work, information and analytical work, management.